The Performance of Activated Natural Zeolitess for Color Adsorption of Naphthol and Heavy Metal Cr Used in Batik Industry - Christine Indira Rinai Pangesti (Waste Technology)
One of the most developed industry in Indonesia is batik industry. Batik industry in 2006 amounted to 48,287 business units spread over 17 provinces, and employed 792,300 people. The main source of waste in the batik industry is the use of dyes which are known to contain heavy metals Cr and naphthol dyes. One of the absorbents that can be utilized is natural zeolites. In this research there will be wastewater treatment of batik industry in the form of synthetic solution containing heavy metal Cr and naphthol dyes with adsorption method using natural zeolites. The research method using experimental method with quantitative descriptive data. This research used different heating treatment for zeolites activation process, namely 1500, 3000, 4500 and 600 0C. Unsaturated zeolitess will be compared with their adsorption effectiveness by absorbance measurement method using UV-VIS spectrophotometer and atomic absorption spectrophotometer. From this research that has been done, it is expected to know the effectiveness of adsorption from the two natural zeolitess from    Purworejo and   Ponorogo to the adsorption ability of naphthol dyes and heavy metals Cr. So it can be known that natural zeolites has better adsorption ability comes from Ponorogo.Key words: Adsorption, Batik Waste,  Natural Zeolitess, Zeolites Activation